2020
DOI: 10.1098/rspa.2020.0111
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous convection in porous media

Abstract: The problem of convection in a fluid-saturated porous medium is reviewed with a focus on ‘vigorous’ convective flow, when the driving buoyancy forces are large relative to any dissipative forces in the system. This limit of strong convection is applicable in numerous settings in geophysics and beyond, including geothermal circulation, thermohaline mixing in the subsurface and heat transport through the lithosphere. Its manifestations range from ‘black smoker’ chimneys at mid-ocean ridges to salt-desert pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 137 publications
(303 reference statements)
0
56
0
Order By: Relevance
“…Hewitt, Neufeld & Lister 2014; Loodts, Rongy & De Wit 2014). For example, Hewitt (2020) gives a recent review of their applications to vigorous convection in porous media.…”
Section: Governing Equationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hewitt, Neufeld & Lister 2014; Loodts, Rongy & De Wit 2014). For example, Hewitt (2020) gives a recent review of their applications to vigorous convection in porous media.…”
Section: Governing Equationsmentioning
confidence: 99%
“…2014; Slim 2014; Hewitt 2020). Similarly, in many cases a slab geometry of fixed height is modelled, where a scaling based on the layer thickness can be made (Ruith & Meiburg 2000; Riaz & Meiburg 2003; Hewitt 2020). We will instead follow a scheme where and where the group in (2.6) reduces to the Rayleigh number, .…”
Section: Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow pattern and flux in buoyancy-driven porous-media flow have received much attention, for its relevance to various processes in nature and industry, such as geothermal energy recovery and geological sequestration of carbon dioxide (Huppert & Neufeld 2014;Hewitt 2020). Recently, it has been found that hydrodynamic dispersion has a significant effect on the flow properties of porous-media convection (Hidalgo & Carrera 2009;Emami-Meybodi, Hassanzadeh & Ennis-King 2015;Wen, Chang & Hesse 2018;De Paoli, Alipour & Soldati 2020).…”
Section: Introductionmentioning
confidence: 99%